Two Ecospheres, One Literature: Post-1965 Developments in Malay Literature in Singapore and Malaysia (Malay Literature, 2014)
Before 1965, Malay literature in Singapore and Malaysia was a single, shared entity. In fact, for a while, Singapore was one of the major centres of literary development, particularly through the endeavors of authors in Angkatan Sasterawan 50 (Asas 50) and friends in media and film. Singapore's withdrawal from Malaysia in 1965 was an event that brought major changes, especially for Malay literature in Singapore. However, as this article hopes to show, although the split gave rise to far-reaching influences and two different socio-political ecospheres, activists of Malay language and literature in Singapore have persevered. Along with Malaysian activists and institutions, they continued to develop and enrich a shared Malay literature. For this purpose, the article will study historical developments in Singapore and Malaysia since 1965, particularly the diligent efforts, plans and activities to ensure that Malay literature continues to develop uninterrupted in Singapore. It also shows that the unity of the nations' literatures are not fragmented, but instead can continue to develop as one literature. Results of the observation show that early awareness, planning, strategy, positive action and determination have ultimately succeeded in nurturing and developing one Malay literature in Singapore and Malaysia that produces manifold results.Keywords: Malay literature, Singapore, Malaysia, socio-political ecosphere, cooperation